Ejecución del gasto en expedientes técnicos y su relación con la ejecución de obras de infraestructura del Gobierno Regional de Loreto periodo 2019 – 2023 - Da Silva del Aguila, Victor Oswaldo (2025)
Investment in infrastructure plays a fundamental role in the economic development and well-being of a nation. However, deficiencies in technical files and public works can be attributed to a series of interrelated factors that include lack of planning, poor or incomplete designs, insufficient supervision during execution, among others. Therefore, the study aims to identify how spending on technical files is related to the execution of infrastructure works of the Regional Government of Loreto period 2019-2023, with a non experimental correlational research design with a quantitative and observational approach, with a population made up of the economic information of the regional government of Loreto, identifying that between 2019 and 2023, spending on technical files is significantly and positively related to the execution of infrastructure works of the Regional Government of Loreto period 2019-2023. The research concludes that the analysis carried out on the relationship between spending on technical files and the execution of infrastructure works in the Regional Government of Loreto during the period 2019-2023 shows a significant and positive correlation, highlighting the importance of an adequate allocation of resources to guarantee the success of the projects. The determined resources were the main source of financing, representing 76.8% of the total, with a peak in 2022, while ordinary resources and official operations had a limited contribution. Educational facilities concentrated 66.2% of total spending, followed by medical facilities at 32.6%, leaving other types of infrastructure in the background. However, in works on non-residential buildings and other structures, although positive correlations were observed, these were not statistically significant, evidencing the need to improve technical and administrative processes to strengthen the execution of these projects.